Enhancing Fourth-Grade Elementary Students Mathematical Reasoning Skills Through the SAVI Model - Viantorus, Verrill Adha Vi; Wibowo, Setiawan Edi; Firdaus, Fery Muhamad (FKIP Universitas Lampung, 2024)
Enhancing Fourth-Grade Elementary Students Mathematical Reasoning Skills Through the SAVI Model. Objective: This study aimed to evaluate the impact of the Somatic, Auditory, Visual, Intellectual (SAVI) model on the mathematical reasoning skills of fourth-grade students in the context of fractions and to compare its effectiveness with the Numbered Heads Together (NHT) cooperative learning model. Methods: A quantitative research approach with a quasi-experimental design was adopted. The study population comprised 100 fourth-grade students at SD Muhammadiyah Bogor, from which 50 students were selected through purposive sampling. Class IV A served as the experimental group, employing the SAVI model, while Class IV B acted as the control group, utilizing the NHT model. Data collection was conducted through validated pretests and posttests using a mathematical reasoning test with established reliability. Findings: The data analysis indicated a significant improvement in the mathematical reasoning abilities of the experimental group, which achieved a